Alteración en el desarrollo de los reflejos primitivos y su implicación en las habilidades visuales: Revisión narrativa (2024)
Primitive reflexes are automatic and involuntary movements which contribute to the neuromotor development of the child from the first weeks of life, they have an age of onset and inhibition, if they are maintained beyond that age, they can cause alterations in development due to affection in the CNS (central nervous system). Objective: To identify the visual alterations associated with the persistence of primitive reflexes in a pediatric population diagnosed with prematurity, spastic cerebral palsy and healthy at term. Methodology: A bibliographic search was carried out in databases (Pubmed, Scopus and Google Scholar), in relation to the systemic and/or visual alterations present in children with persistent primitive reflexes, through equations established for each database.